Pakistan’s changing demography: Urbanization and peri-urban transformation over time - Kedir Jemal, Mekamu; Schmidt, Emily; Wagas, Ahmad (International Food Policy Research Institute, 2016)
This study uses Geographic Information Systems (GIS) to evaluate improvements in transportation infrastructure and related urbanization over the last 40 years in Pakistan. In addition, we suggest a definition to measure peri-urban population using the agglomeration index methodology developed by Uchida and Nelson (2008). In doing so, we incorporate a series of GIS data including: travel time rasters, population density rasters and other nationally collected biophysical and infrastructure variables (i.e. roads, railroads, waterbodies) in order to construct measurements of urban agglomeration within Pakistan. We use road and population data from corresponding census years (and government growth rates for more recent population estimates) to model reductions in remoteness to urban areas over time.